Educational Diversity and Knowledge Transfers via Inter-Firm Labor Mobility - Marianna Marino; Pierpaolo Parrotta; Dario Pozzoli (Institute for the Study of Labor (IZA), 2014)
This article contributes to the literature on knowledge transfer via labor mobility by providing new evidence regarding the role of educational diversity in knowledge transfer. In tracing worker flows between firms in Denmark over the period 1995-2005, we find that knowledge carried by workers who have been previously exposed to educationally diverse workforces significantly increases the productivity of hiring firms. Several extensions of our baseline specification support this finding and show that insignificant effects are associated with the prior exposure of newly hired employees to either demographic or culturally diverse workplaces.
Keywords: J24; J60; L20; 330; educational diversity; knowledge transfer; inter-firm labor mobility; firm productivity